Features Associated With Quality of Life Impairment in Hidradenitis Suppurativa Patients - Schneider-Burrus, Sylke; Tsaousi, Athanasia; Barbus, Sebastian; Huss-Marp, Johannes; Witte, Katrin; Wolk, Kerstin; Fritz, Björn; Sabat, Robert (Frontiers in Medicine, 2021)
Background: Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease with an adverse impact on patients’ quality of life (QoL). Objectives: To quantify QoL impairment in patients in Germany suffering from HS and to identify the parameters associated with QoL impairment. Methods: A non-interventional, cross-sectional, mono-centric study with 500 HS patients. QoL data (measured using the Dermatology Life Quality Index; DLQI) and demographic, anamnestic, clinical, and blood parameters were collected. All patients were examined by dermatologists that documented the skin alterations. QoL data from 462 HS patients were available and evaluated. Results: The mean (± standard error) DLQI score of HS patients was 13.18 ± 7.99. Approximately 40% and 20% of HS patients declared very large and extremely large QoL impairment, respectively. The degree of QoL disturbance correlated with the severity of skin alterations, blood leucocyte count, in particular, with anogenital localization, and the presence of nodules and fistulas. Furthermore, QoL impairment was associated with specific comorbidities, such as adiposity and back pain, but not with HS family history. QoL impairment in HS patients was not influenced by whether or not the patients had undergone resection surgery or antibiotic treatment but was more severe in HS patients that had undergone abscess lancing compared to patients without such treatment in the past. Limitations: It was a mono-centric study and most data were obtained from self-administered patient questionnaires. The association of QoL with type of treatment was analysed for abscess lancing, resection surgery, and antibiotic treatment. Further therapeutics modalities recommended in the guidelines were not investigated. Conclusion: A profound impairment in QoL was present in patients with HS, and this was higher than that observed in other studied dermatoses. The degree of impairment correlated with the extent of cutaneous and some extra-cutaneous alterations. Surgical and conventional medicamentous therapy of HS was not associated with long-lasting reduction of QoL impairment. Our data support the implementation of patient-reported outcome measures for the assessment of therapy responses.